Odpowiedzi

Najlepsza Odpowiedź!
2010-02-21T18:19:47+01:00
A)
2y=9+3
2y=12/2
y=6
7x+2*6-3=9
7x+12-3=9
7x=9-9
7x=0/7
x=0
z=3

b)klamra i skreśl y w pierwszych 2 równaniach
2x-y=-2
y-4x=0
2x-4x=-2
-2x=-2/-2
x=1
2-y=-2
-y=-2-2
-y=-4/1
y=4
1+4+z=0
5+z=-5
z=-5
y=4
x=1
z=-5

2010-02-21T18:31:59+01:00
A.)
7x+2y-z=9
-2y-z=-1
z=3
-2y-3=-1
-2y=2
y=-1
7x+2*-1-3=9
7x+-2-3=9
7x=14
x=2

x=2
y=-1
z=3

b.)
x+y+z=0
2x-y=-2
y-4x=0
y=4x
2x-4x=-2
-2x=-2
x=1
y=4x
y=4
z=-x-y
z=-1-4
z=-5

x=1
y=4
z=-5

c.)
x+y-z=-10
x-y+z=4
x+z=4
y = 0 --> 0 ponieważ w 2 równaniach bez y i z daje ten sam wynik
x-z=-10
x+z=4
2x=6
x=3
3+z=4
z=1

x=3
y=0
z=1